CONFLICTOLOGICAL CULTURE OF PERSONALITY IN A PROFESSIONAL ENVIRONMENT (BY THE EXAMPLE OF PEDAGOGUES AND ENGINEERS) - Shcherbakova, Olga; Tatarinceva, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The levels of conflictological culture of pedagogues and engineers, the peculiarities of its formation as well as the comparison of the conflictological culture’s levels among representatives of these specialties on the base of their gender and work experience are analyzed in the proposed research. Each specialist owns a certain level of the conflictological culture’s development and he/she expresses it in a professional environment. The relevance of the research’s theme is caused by the necessity to improve conflictological culture of specialists for their further successful activities. The Aim of the research is the identification of differences in the levels’ formation of specialists’ conflictological culture by the example of pedagogues and engineers and the influence of such a characteristic as a gender and work experience  on it. The Object of the research is the process of forming conflictological culture of pedagogues and engineers. The Methods of the research are the following:1. the theoretical analysis of scientific literature on the given problem;2.the empirical analysis of obtained data reflected the level’s formation of pedagogues and engineers.